Loperamide overdose causing torsades de pointes and requiring Impella temporary mechanical support: a case report. Issue 4 (27th September 2019) - Cicci, Jonathan D; Jagielski, Sarah M; Clarke, Megan M; Rayson, Robert A; Cavender, Matthew A
Abstract: Background: Loperamide is a widely available oral μ-opioid receptor agonist, and loperamide abuse is increasing by those seeking intoxication. Loperamide has potent QTc-prolonging properties, placing patients at risk for ventricular arrhythmias and sudden cardiac death. Case summary: A 23-year-old woman was found to be in pulseless ventricular fibrillation with a QTc of 554 ms and received multiple defibrillations and IV lidocaine. Her toxicology studies were negative. She subsequently experienced multiple episodes of torsades de pointes and was found to be in cardiogenic shock with a left ventricular ejection fraction of 5%. Following multiple defibrillations, an Impella® mechanical circulatory support device was placed, and she was given IV magnesium and IV lidocaine. After mechanical circulatory support was withdrawn, she experienced major bleeding and was found to have a deep vein thrombosis, bilateral radial artery thrombosis, and multiple pulmonary embolisms in the setting of heparin-induced thrombocytopenia. After stabilizing, she admitted to taking 80 tablets of loperamide 2 mg in pursuit of euphoria. Discussion: Loperamide is an increasingly popular agent of abuse. Loperamide-associated ventricular arrhythmias are rare with normal doses but more common with high doses, chronic ingestion, or interacting medications. Loperamide cardiotoxicity may be prolonged due to a long half-life and accumulation. Loperamide abuse may be under-recognized, leading to delays in treatment. Intravenous fluids, magnesium supplementation, chronotropes, transcutaneous or transvenous pacing, and defibrillation may be helpful in mitigating loperamide-associated polymorphic ventricular tachycardia. Clinicians should monitor for drug interactions in patients taking loperamide and screen for electrocardiographic abnormalities in those taking chronic or high-dose loperamide.